Actigraphy‐measured nocturnal wrist movements and assessment of sleep quality in patients with bullous pemphigoid: a pilot case–control study. (16th January 2019) - Kalinska‐Bienias, A.; Piotrowski, T.; Kowalczyk, E.; Lesniewska, A.; Kaminska, M.; Jagielski, P.; Kowalewski, C.; Wozniak, K.
Summary: Background: Bullous pemphigoid (BP) is a distressing autoimmune bullous disease strongly associated with severe pruritus; however, data concerning pruritus in BP are still scarce. No clinical research evaluating the effect of BP on sleep quality has been conducted. Aim: To evaluate the intensity of pruritus measured by nocturnal wrist movements (NWMs) and the sleep quality in patients with BP using actigraphy in comparison with nonpruritic healthy controls (HCs) with subsequent correlations with an itch visual analogue scale (VAS) as a subjective measure, disease severity [Bullous Pemphigoid Disease Area Index (BPDAI), urticaria/erythema, erosions/blisters] and serum total IgE level. Methods: In total, 31 patients with newly diagnosed BP (mean ± SD age 75.4 ± 12.3 years) and 40 nonpruritic HCs (age 73.5 ± 11.7 years) were recruited. All participants wore a sleep monitor (ActiSleep+) on the dominant wrist. Results: For patients with BP, median VAS score was 5.5 and median BPDAI was 43 (urticaria/erythema BPDAI was 16, erosions/blisters BPDAI was 29). Scratching, defined as bouts of NWMs, was significantly ( P  < 0.001) more intensive in patients with BP than in controls. Characteristic of BP was that scratching bouts corresponded with the slowest wrist movements. There were no correlations with VAS, BPDAI or total IgE level. Compared with HCs, patients with BP presented significant ( P  < 0.001) sleep disturbances, as determined by sleep efficiency, waking after sleep onset and average duration of awakening, and these were strongly correlated with urticaria/erythema BPDAI. Conclusion: Nocturnal wrist movements measured by actigraphy are more intensive in patients with BP than in nonpruritic HCs, and characteristically slow movements. Actigraphy method showed very low sleep quality in patients with BP, thus severity of BP has a negative impact on sleep.